Towards an Inclusive and Accessible Digital Scholarly Editing: A Critical Assessment (Journal of the Digital Humanities Association of Southern Africa, 2024)
This paper is based on an ongoing project on Diversity, Inclusivity, Accessibility in Digital Scholarly Editing (DIA-DSE and in our view it should be seen as a place of critical assessment of existing digital scholarly editions (DSE) and discussion for future developments and improvement. Our idea is the result of a bigger initiative based at the University of Verona (Italy) on the topic Inclusive Humanities: Perspectives of Development in Research and Teaching Foreign Languages and Literatures [1]. In its essence it tries to respond to some of the goals envisaged by globally relevant agendas and strategic plans which put in the foreground the challenges posed by our time and focuses on the idea that a knowledge society like ours needs to develop an open model of science. This novel model pleads for an accessible science and through innovative methodologies seeks to involve wide, inclusive and diverse agents, contents, and targets into the scientific discourse. In this context, our aim is to investigate from the perspective of Diversity, Inclusivity and Accessibility (which we call by the acronym DIA) a traditional field of study, that is philology and textual criticism, in its very ultimate development: Digital Scholarly Editions (DSE). The field of DSEs raises nowadays the following questions: Do DSE projects consider Diversity, Inclusivity and Accessibility? If so, how much and how do they do this? To try to provide an answer, in the context of DIA-DSE project we will build a corpus of existing resources and we will try to assess their DIA degree according to different parameters. In the long term, after data collection and analysis, a ranking of diverse, inclusive and accessible resources will be defined. These results will be followed by a survey that will be disseminated among the scholarly community and users, with the objective engage in an open critical discussion, to raise awareness and to gain suggestions for the creation of DIA-DSE guidelines that will be published and promoted at the end of the project.
Keywords: Digital Scholarly Editions; Web Accessibility Initiative; Inclusivity